2017
DOI: 10.31018/jans.v9i2.1305
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in tomato (Solanum lycopersicum L.) genotypes revealed by simple sequence repeats (SSR) markers

Abstract: Twenty five tomato (Solanum lycopersicum L.) genotypes were subjected to genetic diversity analysis using twenty SSR markers. Out of 20 markers used, 14 SSRs were polymorphic and a total numbers of 22 SSR alleles were generated by 14 SSR markers, out of which 19 were polymorphic and 3 were monomorphic, with an average of 1.57 alleles per locus. The range of amplified products was 100-400bp approximately. Jaccard's similarity coefficient varied from 0.65 between germplasm EC519821 and CO-3 to a maximum of 1.0 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Primers CA and GT were not very informative. Kaushal et al (2017) found PIC values between 0,0 to 0,54 with an average of 0,27 in the evaluation of 25 tomato genotypes with 20 microsatellite markers. Likewise, Marin-Montes et al (2019), found an average PIC value of 0,63 when evaluating the genetic diversity of 26 accessions of native Mexican tomatoes with 18 SSR molecular markers.…”
Section: Resultsmentioning
confidence: 91%
“…Primers CA and GT were not very informative. Kaushal et al (2017) found PIC values between 0,0 to 0,54 with an average of 0,27 in the evaluation of 25 tomato genotypes with 20 microsatellite markers. Likewise, Marin-Montes et al (2019), found an average PIC value of 0,63 when evaluating the genetic diversity of 26 accessions of native Mexican tomatoes with 18 SSR molecular markers.…”
Section: Resultsmentioning
confidence: 91%
“…Pusa Ruby, IC-26372, Manulakshmi, Arka Samrat, Arka Alok, Sakthi showed 100% similarity. Kaushal et al (2017) reported a maximum of 96% similarity among tomato. High level of similarity (95%) was revealed among 39 tomato (Al-Abadi, 2007), similarity of 100% was found among tomato (Tam et al, 2005).…”
Section: Similarity Coefficient Analysismentioning
confidence: 98%
“…PCR reaction was performed in a 20μl reaction mixture which consisted of, 2.0 μl of genomic DNA with quantity 25ng/ μl, 2.0 μl of 10X Taq assay buffer A, dNTPs mix (10mm each) of about 1.5 μl, 0.3 μl of Taq DNA Polymerase (1U). 0.75 μl of Forward and reverse primer (10pM) respectively and 12.7 μl of autoclaved distilled water (Kaushal et al, 2017).…”
Section: Pcr Amplification Using Ssr Primersmentioning
confidence: 99%
“…Briefly, microsatellites were used to analyze a wide array of traits like genetic diversity [16,17,18], organoleptic properties [19], delayed fruit ripening [20] to name a few.…”
Section: Applications Of Ssr and Issr Markers In Tomato Breedingmentioning
confidence: 99%